Anatomical and neurochemical bases of theory of mind in de novo Parkinson's Disease. (September 2020) - Orso, Beatrice; Arnaldi, Dario; Famà, Francesco; Girtler, Nicola; Brugnolo, Andrea; Doglione, Elisa; Filippi, Laura; Massa, Federico; Peira, Enrico; Bauckneht, Matteo; Morbelli, Silvia; Nobili, Flavio; et al.
Abstract: Theory of mind (ToM) deficit is a frequent finding in subjects with neurological and psychiatric conditions. While a number of brain regions play a role in ToM, to date the contribution of the diffuse projection systems is less understood. Here, we explored the topographical and neurochemical bases of ToM using multi-tracer molecular imaging and quantitative electroencephalography (qEEG) in a group of 30 drug-naïve, de novo Parkinson's Disease (PD) patients (mean age 73.39 ± 8.93 years, 11 females). ToM was assessed using the "Reading the Mind in the Eyes Task" (RMET), while general cognition with the MMSE. We acquired FDG-PET images (as a marker of regional neurodegeneration), I-123 Ioflupane Single Photon Emission Computed Tomography (123 I-FP-CIT-SPECT, as a marker of dopaminergic impairment in the basal ganglia and in the cortex and as a proxy marker of serotoninergic deafferentation in the thalamus), and qEEG recordings (using the Theta/Alpha power ratio as marker of cholinergic deafferentation). PD presented with a significantly worse RMET score compared to 60 controls (20.7 ± 5.5 vs 27.5 ± 3.0 p  = .001) while there was no difference between the two groups in age, education or MMSE. The voxel-wise analysis of total RMET score and regional metabolism showed a positive correlation in the superior temporal gyrus and in the insula. Among the proxy markers of dopaminergic degeneration, serotoninergic and cholinergic deafferentation, ToM presented only an inverse correlation with 123 I-FP-CIT thalamic specific binding ratio (SBR) values -a proxy serotoninergic marker-which remained significant after correction for FDG metabolism in the areas associated with ToM. On the other hand, MMSE only correlated with qEEG posterior Theta/Alpha power. These findings point to the presence of a specific cortical and neurochemical signature of ToM in PD, to the independence of ToM from general cognition, and suggest possible therapeutic targets to treat social cognition deficits.